Ecotourism: A Mechanism for Sustainable Tourism Development - Maxwell-Borjor Achuk Eba; Dorn Ckiaimz Enamhe (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2023)
An increasing number of studies around the world have stressed that "ecotourism’ is an appropriate form of tourism development that meets several indicators of sustainable tourism development. In order to analyse the aptness of ecotourism, which brings a balance between tourism and sustainable tourism development, an attempt is made to answer the following research question through this work: Does ecotourism, an ideal form of tourism development, satisfy sustainable tourism indicator areas? The research question is answered through comparative case studies. Furthermore, in order to understand to what extent or degree the ecotourism attributes agree with the sustainable tourism indicators, a total of 10 case studies were chosen for this purpose. Some random papers were selected between 2003 and 2015, which made up the case studies from different geographical region of the world. Thus, this paper made use of the method of textual analysis to carry out this research. The results of the case studies indicate that ecotourism meets the sustainable tourism indicators. The three areas used to ascertain the foregoing are: (1) sustainable tourism indicator areas; (2) ecotourism attributes; and (3) ecotourism case studies.